How to build a thought. (5th February 2020) - Rasmussen, Joshua; Bailey, Andrew M.
Abstract: We uncover a surprising discovery about the basis of thoughts. We begin by giving some plausible axioms about thoughts and their grounds. We then deduce a theorem, which has dramatic ramifications for the basis of all thoughts. The theorem implies that thoughts cannot come deterministically from any purely "thoughtless" states. We expect this result to be too dramatic for many philosophers. Hence, we proceed to investigate the prospect of giving up the axioms. We show that each axiom's negation itself has dramatic consequences that should be of interest to philosophers of mind. Our proof of the theorem provides a new guiderail for thinking about the nature and origin of thoughts.